Authorship Trends, Collaboration Patterns, and Co-Authorship Networks in Lodging Studies (1990–2016). Issue 5 (4th July 2018) - Köseoglu, Mehmet Ali; Okumus, Fevzi; Putra, Eka Diraksa; Yildiz, Mehmet; Dogan, Ismail Cagri
ABSTRACT: This study evaluates authorship trends, collaboration patterns, and co-authorship networks in lodging studies. Lodging-related articles published in academic journals from 1990–2016 were searched and about 2647 of these were analyzed using bibliometric analysis. The study findings suggest progressive growth in collaboration in the lodging articles. The characteristics of the co-authorship networks of lodging studies are not much different from those observed in other disciplines. Moreover, the lodging studies' co-authorship networks match the properties of small-world network theory, which influences the diffusion speed of properties. Lastly, authors in the whole period were ranked based on network centrality metrics, such as degree centrality, Bonacich's power index, closeness centrality, and betweenness centrality. As one of the first studies in this field, the research findings presented here provide specific theoretical and practical implications, with limitations, and the potential for expansion in future studies.